1980
DOI: 10.1136/jech.34.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Growth profile of preschool children in an Indian rural community.

Abstract: PradeshSUMMARY An investigation into the nutritional anthropometry of preschool children of poor socioeconomic status was carried out in a rural community of India by door-to-door visits. All measurements-height, weight, left mid-arm girth, and chest and head circumferences-were far below local as well as international standards. By comparison with the Harvard standard, about 53% of the children were below it in respect of height for age and about 82% in respect of weight for height. The proportion of undernou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…He found that maximum growth spurt in height was in the age group 10-11 years Better socioeconomic and living conditions, optimal health care, and adequate nutrition brings better health has been observed by many workers." [19]Children of Low socio-economic income group lag very much behind the High socio-economic group. These underprivileged children are constantly exposed to severe nutritional, social and environmental strains as revealed in the present study and the studies done earlier.…”
Section: Discussionmentioning
confidence: 99%
“…He found that maximum growth spurt in height was in the age group 10-11 years Better socioeconomic and living conditions, optimal health care, and adequate nutrition brings better health has been observed by many workers." [19]Children of Low socio-economic income group lag very much behind the High socio-economic group. These underprivileged children are constantly exposed to severe nutritional, social and environmental strains as revealed in the present study and the studies done earlier.…”
Section: Discussionmentioning
confidence: 99%